The influence of material variability on the strength of cold “in situ” pavement recycling with cement - Oliveira, Joel (2009)
Environment preservation associated to economic issues have led recycling to be a prime solution for pavement maintenance/rehabilitation. The present work focuses on the analysis of a rehabilitation project that included a recycled base course with cement. The operations involved cold “in situ” recycling of part of the existing bituminous layers and of the top part of the granular layers with the addition of cement and overlaying with new bituminous mixtures. Before the rehabilitation, significant thickness variability was observed in the existing layers, which highlighted the need for an assessment of the bearing capacity of the resulting recycled base course and its tensile strength. In order to determine the factors that most influence the final properties, a laboratory study, in which specimens with controlled composition were prepared and tested, was carried out. The results showed that small amounts of soil, especially organic soil, reduce drastically the strength of the recycled material.